Warning: May Contain Politics. Poems on Diversity, Social Justice and Community Involvement by Jo McFarlane (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
This book is not for the faint-hearted, as evinced by the cover which features a saltire with the iconic image of Che Guevara printed across it. At the beginning, the poems are more polemical than poetic and not for the poetry purist. However, the politics and and sentiments are where the book’s power lies, and we are introduced straight away with two personal/political pieces, both based in Edinburgh. The first one uses the letters of her name to spell out a wish list for the opening of the Scottish parliament. The second is an angry lament set in a protest at the mound with a regretful twist at the end expressing her chagrin at not having been there.